KESADARAN HUKUM DALAM BELA NEGARA DAN CINTA TANAH AIR (NKRI) BAGI PASIEN PROLANIS KLINIK PRATAMA ”RAHMATIKA” SEMARANG - Muzayanah (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The Republic of Indonesia is an independent, united, sovereign, just and prosperous country. As the Unitary State of the Republic of Indonesia (NKRI), Indonesia is an independent country which was proclaimed on August 17, 1945. As an independent country, the Indonesian state has the right to regulate and administer the state administration system of the Republic of Indonesia based on the state constitution, namely the 1945 Constitution. an independent Indonesian state, it is necessary to pay attention to all Indonesian citizens so that this country continues to develop and progress as aspired in the fourth paragraph of the opening of the 1945 Constitution. Awareness in the nation and state must be realized by carrying out State Defense and love for the homeland in the Unitary State of the Republic of Indonesia. , so that our country remains an independent, just and prosperous country based on Pancasila and the 1945 Constitution. State defense is a form of public awareness to participate in maintaining security in their respective environments according to their capacity and profession. ng each. State defense can be carried out by maintaining the safe situation of each family and carrying out its activities as the smallest community unit in a country. The next question is whether the residents of Prolanis Patients at the